Model Pembelajaran Kooperatif Tipe Make A Match dalam Pendidikan Agama Kristen - Rinto Hasiholan Hutapea (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2020)
This study aims to determine the concept of using a make a match type of cooperative learning model in learning Christian Religious Education. The method used in this research is descriptive qualitative method. The study results obtained illustrate that the use of a make a match type of cooperative learning models in classroom learning, can increase learning motivation and student learning outcomes. In dealing with the problem of low Christian Religious Education teachers and students’ learning motivation towards Christian Religious Education subjects, the use of a make a match type of cooperative learning model is an alternative choice in teaching. Using this learning model in overcoming these problems, Christian Religious Education teachers need some effort so that its implementation can be effective. These efforts are: first, a Christian Religious Education teacher needs to increase creativity. Second, Christian Religious Education teacher need to pay attention to their competence in teaching. Third, Christian Religious Education teacher have the principle of continuing to learn and develop themselves according to current needs. Abstrak Penelitian ini bertujuan untuk mengetahui konsep penggunaan model pembelajaran kooperatif tipe make a match dalam pembelajaran Pendidikan Agama Kristen. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif. Kajian hasil penelitian diperoleh gambaran bahwa penggunaan model pembelajaran kooperatif tipe make a match dalam pembelajaran di kelas, dapat meningkatkan motivasi belajar dan hasil belajar peserta didik. Guru PAK dalam menghadapi masalah rendahnya minat dan motivasi belajar peserta didik terhadap mata pelajaran PAK, penggunaan model pembelajaran kooperatif tipe make a match menjadi alternatif pilihan dalam mengajar. Penggunaan model pembelajaran ini dalam mengatasi persoalan tersebut, guru PAK memerlukan beberapa upaya agar pelaksanaannya menjadi efektif. Upaya tersebut adalah: pertama, seorang guru PAK perlu meningkatkan kreativitas. Kedua, guru PAK perlu untuk memperhatikan kompetensi diri dalam mengajar. Ketiga, guru PAK memiliki prinsip untuk terus belajar dan mengembangkan diri sesuai kebutuhan pada masa kini.